PENERAPAN RAMAH DIFABEL DALAM PELAYANAN PERPUSTAKAAN SASTRA MANGUTAMA - Suhartika, I Putu; Putra, Kadek Aryana Dwi; Haryanti, Ni Putu Premierita (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2022)
Librarians deserve good service from the library. However, not all libraries have disabled-friendly services. This study aims to evaluate the disabled services provided for persons with disabilities at the Mangutama Literature Library, the Archives and Library Office of Badung Regency. The method used is descriptive qualitative with data collection through interviews, field observations, documentation and literature study. Informants in this study were librarians and users of the Mangutama Literature Library, Badung Regency Archives and Library Office. The results showed that the service management for the disabled was not optimal, as seen from the unavailability of guiding blocks or special floor directions intended for the blind, the lack of special computers and special library materials for the disabled.